Model Pendugaan Biomassa Dan Karbon Hutan Rakyat Jati Unggul Nusantara (Kasus Hutan Rakyat Jati Unggul Nusantara (JUN) Umur 5 Tahun Desa Trosono, Kecamatan Parang Kabupaten Magetan) - Lukito, Martin; Rohmatiah, Ahadiati (JURNAL AGRI-TEK, 2014)
JUN have important role in the conservation and see the economic advantages such as root crops JUN stable compoun, Produce fast-growing plants , with quality timber products from aspects of conservation and can be harvested from the age of 5 years from the economical aspects . The purpose is the potential magnitude Predicting wood and plant biomass potential JUN.dan carbon content stored in various plant organs, the magnitude of the potential suspect plantation forests to absorb CO2 . The study was conducted on public forests in the village Trosono JUN plants . District. Parang . Kab . Magetan , through forest inventore . The results : Estimated potential stand stand for community forest plants ranged JUN 288.74 m3 , or with an average of 87.667 m3/ha average volume of 0.1337 m3/ tree with the smallest volume of 0.00789 m3 and Smallest volume of 0.0045 m3 and the largest of 0.7387 m3 . The total potential of biomass is 56.2 tons . Or the equivalent of 17.295 tons/Ha . The composition of the biomass plant organs on the trunk of 53.84 % by weight of the total biomass , while root occupies second place at 19.55 % , 16.01 % and a branch of the most smallest leaves at 10.60 % . Average carbon content of the sample stands of trees ranged from 7.86 kg , ranging from 8.73 tons of Co2/ha composition of plant organs in organ stem reaches 53.14 % of the total carbon content of trees , followed by 19.29 % roots , Branch 15:30 % , and leaves of 10:46 % . CO2 sequestration potential when converted to the number of plants per hectare on average 31.97 tons CO2/ha . Allometric equation which is derived in this study as follows .Keywords : Potential , Biomass ; carbon dioxide , CO2 absorption ,